Balancing Our Identities as Medical Students and Global Citizens in the Wake of COVID-19. - Ramesha Ali (University Library System, University of Pittsburgh, 2020)
As medical students, we felt the burden of COVID-19 in two distinct waves. The first wave brought with it a loss of opportunity and the immense sadness that came with the understanding that we would move forth without ever compensating for such experiences. As clerkships and licensing exams were slowly canceled, we struggled to find ways to fill our days and continue to remain strong postgraduate candidates. It was not long before our personal losses became insignificant in the face of the global trajectory COVID-19 took and the burden of the pandemic impinged on our vulnerabilities. Suddenly, we were facing a significant loss of life and the fear of ill-health was ever-present. This challenged our identity as medical students and forced us to identify as global citizens who were also susceptible to the threat of the pandemic. It also forced us to uphold our health and well-being just as we had pledged to hold the health and well-being of others and to include ourselves in our commitment to a lifetime of service.